Água da chuva e desenvolvimento local: o caso do abastecimento das ilhas de Belém - VELOSO, Nircele da Silva Leal (Universidade Federal do Pará, 2013)
Water is a natural resource of significant economic, social, environmental and in many cases also cultural. Regions are suffering water shortages, both in quantity and quality. The Amazon, ironically known as a reserve of water resources, is also hostage to the lack of access to clean drinking water. The water supply in the islands of Belém is poor and propose alternatives that will ensure access to decent water quality is a major challenge. In this sense, the objective of this study is to evaluate the feasibility of the use of rainwater for potable supply in the islands and Grande and Murutucu as a way of promoting local sustainable development. For this, we carried out to characterize socioeconomic survey of the forms of water applied in the area, as well as analysis of the perception of the riverine and the use of rainwater, according to aspects of acceptability and interest in acquiring. It was found that 43% of riparian needs are remedied by buying potable water coming from wells (not proven), which spends about 11% of family income, spending more than the residents of Belém with water. Still on supplies nearly 20% consume water from the river. The investigation revealed that the Grande Island about 45% of the population being treated through the water, another area in this figure is 30%. It was found that 61.4% of residents of Grande Island are in favor of consumption of rainwater, since the island Murutucu portion corresponds to 50.4%. The aspect that inhibits the use of rain water is the taste. Although environmentally and socially viable, the proposed system proved financially unfeasible since most of the population earn less than a minimum wage, thus the system is partly possible.